Traditional Chinese medicine as potential adjuvants for tumor vaccines: a review of types, mechanisms, and forms - Cui, Yongjia; Gong, Lutian; Chang, Lei; Lu, Wenping; Zhao, Siqing; Zhuo, Zhili; Zhang, Xiangyang (Frontiers in Immunology, 2025)
Therapeutic cancer vaccines are increasingly recognized as a highly promising approach for tumor treatment; however, their clinical efficacy critically depends on the rational design of vaccine adjuvants. Natural compounds derived from Traditional Chinese Medicine (TCM) have emerged as attractive candidates for next-generation tumor vaccine adjuvants. In this review, we systematically summarize the chemical constituents of TCM-derived adjuvants reported in current research and categorize their mechanisms of action into four functional modalities: (i) immunostimulatory adjuvants that activate innate immune pathways; (ii) delivery-enhancing systems that improve antigen stability and facilitate targeting to antigen-presenting cells; (iii) integrated platforms that combine both immunostimulatory and delivery-enhancing functions; and (iv) other mechanisms involving non-canonical immunomodulatory activities. We further discuss current challenges in standardization, regulatory approval, and clinical translation, offering a roadmap for harnessing the potential of TCM in the rational design of cancer vaccines.